Conceptual Reconstruction of Fatherhood in Early Childhood Care: The Perspective of the Qur’an and Hadith as the Foundation of Contemporary Islamic Parenting Models - Wicy Elvi Septiani; Rita Mariyana; Badru Zaman; Mubiar Agustin (Universitas PGRI Yogyakarta, 2026)
The phenomenon of fatherlessness and the limited literature reconstructing the role of fathers in early childhood caregiving thematically represent a serious challenge in early childhood education studies. To date, the role of fathers is often confined to the financial function within the family, namely, as breadwinners. Meanwhile, the role of fatherly caregiving in Islam has received relatively little attention in the academic world. Therefore, this study aims to conceptually reconstruct the role of fathers in early childhood caregiving based on the perspective of the Qur’an and Hadith. The research uses a qualitative approach, drawing on a literature review of Qur’anic verses and Hadiths as primary sources. This study also cites articles from indexed journals, including Scopus and Google Scholar, published during the 2020–2025 period as secondary sources. The study identified three main roles of fathers in early childhood parenting: as a protector both physically and psychologically; as a provider of material needs, emotional support/affection, leisure time for bonding, and assistance when the child needs it; and as an educator in all aspects of the child's life, such as being a role model, a spiritual guide, or an academic instructor at home. The novelty of this research lies in a comprehensive, thematic reconstruction of the role of fatherhood that differs from previous literature, which remains partial. Implicatively, this study offers a comprehensive model of Islamic fatherhood as an alternative to social assumptions about fathers' roles, while also providing a conceptual and practical foundation for early childhood parenting today. This model emphasizes that fathers' involvement is a crucial foundation in shaping a child's identity from an early age. Keywords: conceptual reconstruction, early childhood care, fatherhood, Quran and Hadith